Essays in entry, exit and international trade - McGowan, Danny (2011)
Firm entry and exit has been shown to strongly influence productivity growth. Productivity has been identified as the key driver of long-run economic growth. This thesis strives to understand the causes of entry and exit and the role played by globalisation in this process of creative destruction.